The Possible Pathological Role of Endogenous Cannabinoid System in Heart Failure Syndrome - Katerenchuk O. (Львівський клінічний вісник)
Introduction. Heart failure is a clinical syndrome associated with the high rates of short-time and long-time mortality. The pathological role of several neurohumoral systems is well-established in heart failure progression. According to the data available from the basic experiments the role of the endogenous cannabinoid system in heart failure progression is considered. Aim. To make a review of literature and topical scientific sources regarding the possible pathological role of endogenous cannabioid system in heart failure syndrome. Materials and methods. Content analysis, method of system and comparative analysis, bibliosemantic method of research of actual scientific researches on the possible pathological role of endogenous cannabioid system in heart failure syndrome were used. Results. So we have found that several pathological processes in heart failure syndrome are the consequences of endogenous cannabinoid system influence on the hemodynamic. For the majority of patients with the end-stage heart failure a strong and progressive loss of appetite and weight are observed. There are no doubt that this fact can be explained by impaired liver function as the phenomena of “congestion liver,” but this is probably also due to the hyperactivation of endogenous cannabinoid system. As its known, the activation of cannabinoid system due to the activation of CB1 receptors causes an increase in appetite, changes in metabolism of adipose tissue and further leads to obesity. The drug rimonabant was studied as a central cannabinoid receptor blocker as blocking the CB1 receptors that results in the loss of appetite and weight. Heart failure is a condition associated with the hyperstimulation of cannabinoid receptors and/or the depletion of effects of the mediators on them, which leads to loss of appetite and weight. Heart failure is associated with the development of abnormal liver function, elevated liver enzymes and progressive fibrosis process in liver. Also the hyperactivation with further depletion of CB1 is strongly related with the progressive cirrhotic process in the liver as it was observed in several experiments on mice. Depression. For most patients with the high functional class of heart failure the development of depression is usually observed. According to the own observations, among the patients with heart failure NYHA I the depression rate is not more than 5,0 %, in NYHA II – 12,0 % in NYHA III – 40,0 %, in NYHA IV – up to 70,0 %. Theoretically, this could be due to hyperactivation and further depletion of CB1 stimulation in the central nervous system, as its known that stimulation of the CB1 causes euphoria, inhibition/depletion leads to depression. Pain. The acute decompensation of chronic heart failure does not often accompany the patients’ complaints on pain of muscular origin. CB1 receptor activation is known to lead to stable analgesia, inhibition/depletion – to the pain. Conclusions. The hyperstimulation with further depletion of CB1 receptors and mediators results in hypotension, bradycardia, depression, muscle pain and liver cirrhosis – that usually accompanies the decompensated and end-stage heart failure. Further discovering of CB1 exogenous agents acting on central nervous system and/or peripheral CB1 receptors can result in creating the new group of drugs in heart failure treatment.